Technological development as a driver of economic growth in a macro-region - Batov, Gumar Kh.; Zarema U. Temirova, Saida K. Shardan, (Opción, 2019)
The research objective is to show the state of technology and technological development of the North Caucasian Federal District (NCFD) and to identify the factors impeding it. The study is based on the systemic approach and the methods of economic and statistical analysis, scientific abstraction, analogies and scientific generalizations. As a result, the economic efficiency of a macro-region can be increased by using new technologies. In conclusion, it is necessary to intensify research activities in the entities and to establish closer cooperation between scientific institutions, educational organizations and manufacturing enterprises